Return from Standing Timber in Project-evaluation Analysis of Maharashtra Project-further Comments - Chowdhary, R. L. (Indian Forester, 1978)
The present paper analyses the divergent view points of Mishra (1971), Sathe & Susaeta (1973) and Mathur (1975) regarding inclusion of revenues from "God given stand," as a project benefit. If the Project Authority is responsible both for exploitation and plantation of the area, it is logical to include revenues from God given stand as Project benefit, for the Forest Department has heen adequately compensated through payment of annual lease rental, Mathur's (1975) plea for according a higher capitalised value by using risk free rate of interest, appears to be, at best, hypothetical, as this does not represent the current opportunity cost of the resources involved. The original authors, as well as their critics, have not taken into account, the non market benefits (e.g. ample and convenient availabi1ity of industrial wood after maturity of plantations, increased job opportunities, infrastructural developments, forest based recreation etc.) or the costs (e.g. risks associated with monoculture like deterioration of soil texture, increased susceptibility to insect damage, etc) and it is to be solemnly hoped that these balance each other. In the absence of adequate data for quantifying such benefits and costs, an alternative approach is to use a lower discount rate than the going market rate of interest of 9Â½ % for benefit stream and a higher than market rate of interest for discounting for cost stream. The choice of the relative magnitudes of these two rates of interest is difficult to determine in the existing state of knowledge and arts and may have to be a matter of political decision till such time, as more data is collected in this regard.